If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(n + 6) = 98 Reorder the terms: 7(6 + n) = 98 (6 * 7 + n * 7) = 98 (42 + 7n) = 98 Solving 42 + 7n = 98 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 7n = 98 + -42 Combine like terms: 42 + -42 = 0 0 + 7n = 98 + -42 7n = 98 + -42 Combine like terms: 98 + -42 = 56 7n = 56 Divide each side by '7'. n = 8 Simplifying n = 8
| 2(6x-7)=-39+7x | | 105=-7(x-8) | | -9-4x=-6x-19 | | 0.8x-1.8=3.9x+1.9 | | 6(1-4m)=-90 | | 5(2+2x)=4(3-3x) | | (4n-7)(8n-7)= | | 17=1+4p | | cos(3x+20)=0.2 | | 240=12x | | ab=9 | | 1=4+p | | 8x^2-12y+4=y+10 | | cos(3o+20)=0.2 | | 4+3x+6=4x-5 | | x+(-10)=-22 | | 27-7r=-(1+3r) | | 20+2p=8+6(-8+2p) | | -5(a+6)=-14-7a | | 2y^2+14=104 | | x(5)=-5-1 | | 2(x+6)=3(x+4)+5 | | 180(n-1)=900 | | -84=7(p-4) | | -105=-7(1-2r) | | -75-18v=-70 | | =9p^5q+6p^4-15p^2q^4 | | -84=6(n-7) | | 2sinxta*n*x-3=0 | | ln(1-x)=2 | | 8m-21=51 | | 8x+8=4-x |